AB0048 The role of adiponectin in the production of il-6, il-8, vegf, and mmps in human endothelial cells and osteoblasts: implications for arthritic joints. (23rd January 2014) - Kim, K.-S.; Lee, Y.-A.; Kim, K.-Y.; Kim, S.-S.; Hong, S.; Song, R.; Yang, H.-I.
Abstract : Background: The role of adiponectin in the pathogenesis of rheumatoid arthritis was previously studied in relation to the production of IL-6, IL-8, vascular endothelial growth factor (VEGF), and matrix metalloproteinases (MMPs) in fibroblast-like synoviocytes (FLS). Objectives: This study was performed to evaluate the contribution of adiponectin to the production of IL-6, IL-8, VEGF, MMP-1, and MMP-13 in human endothelial cells and osteoblasts in arthritic joints. Methods: Cultured human umbilical vascular endothelial cells (HUVEC) and osteoblasts were stimulated with adiponectin (1 or 10 μg/ml) or IL-1β (0.1 ng/ml) in the presence or absence of hypoxia for 24 hrs. The gene expression patterns of culture supernatants and cells were analyzed by ELISA and PCR, respectively. Results: Adiponectin significantly stimulated the expression of VEGF, MMP-1, and MMP-13 in osteoblasts but not in HUVEC, while it significantly stimulated the expression of IL-6 and IL-8 in both HUVEC and osteoblasts. The increase of VEGF expression by adiponectin was significantly higher than that by IL-1β stimulation. The expression of IL-6 and IL-8 in adiponectin-stimulated HUVEC was about 10-fold higher than that of IL-1β, but about 2-fold higher in osteoblasts. In addition, IL-8 expression levels in HUVEC were about 7-fold higher than that of osteoblasts. However, IL-6 levels were similar between the two cell types, suggesting that adiponectin may be involved in the production of IL-8 in endothelial cells, which may play an important role in neutrophil recruitment to arthritic joints. Furthermore, the increases observed in gene expression by adiponectin were differentially regulated by hypoxia. Conclusions: Adiponectin plays a more important role in the production of mediators driving synovitis and joint destruction in endothelial cells and osteoblasts than that of IL-1β at physiological concentrations. References: Arthritis Res Ther 2009, 11 (6):R161 Acknowledgements: Basic Science Research Program through the National Research Foundation of Korea (NRF) (grant numbers 2010-0024089 and 2011-0009061) Disclosure of Interest: None Declared